Irony as a Form of Expression of the Author’s Attitude in the Satire by Mikhail Lermontov “The Feast of Asmodeus“ (Филологический класс, 2014)
Analysis of Lermontov’s satire proves that the irony, penetrating all levels of poetic structure is a special form of expression of the author’s attitude.